Increased unconscious semantic activation in schizophrenia patients with formal thought disorder - Kiefer, Markus; Martens, Ulla; Weisbrod, Matthias; Hermle, Leo; Spitzer, Manfred (Schizophrenia research, 2009)
Formal thought disorder (TD) is a core symptom in schizophrenia, but the underlying neurocognitive mechanisms have yet to be determined. This pilot study tested the hypothesis that unconscious semantic activation in conceptual memory is increased in thought disordered patients with schizophrenia. Twenty-eight right-handed individuals with a DSM-IV diagnosis of schizophrenia or schizophreniform disorder (2 patients) and 14 healthy comparison participants performed lexical decisions on target words that were preceded by semantically related and unrelated unconsciously perceived masked prime words (masked priming paradigm). Fourteen patients showed more severe thought disorder symptoms (TD patients), 14 patients showed weaker TD symptoms (non-TD patients). Groups did not differ significantly with regard to gender, age, education and premorbid verbal intelligence. Rigorous tests demonstrated that the masked word could not be consciously identified in either group. Schizophrenia patients with TD showed increased masked semantic priming in comparison to non-TD schizophrenia patients and healthy comparison participants. The present results suggest that the unconscious automatic spread of activation within semantic memory is increased in schizophrenia patients with TD. Increased unconscious activation of several related concepts may interfere with conscious goal-directed thinking in TD patients.